PENGARUH PENGAKUAN MUTU JASA PROGRAM STUDI DAN PENGAKUAN MUTU INSTITUSI TERHADAP MAHASISWA (STUDI KILAS BALIK) - Yustinus Yuniarto; Michael Christian (Journal of Business & Applied Management, 2016)
Educational institutions in Indonesia are growing in numbers year by year. This results in increasingcompetition. Thus,these institutions had tried to reach standardized recognition to its learning processquality (program of study‟s accreditation ) and institution‟s quality (ISO certification). This researchaims at figuring out empirically the impact of these variables to the students‟ decision (flashbackdecision). Using SPSS 17.0, this research showed that students‟ decision was influenced by therecognition of the program of study‟s quality. On the other side, the decision was not influenced by theinstitution‟s quality. Generally, further research needs to elaborate other related factors such as therecognition in achieving IWA 2 or the image of the accreditation bodies.Keywords : department’s quality, institution’s quality, accreditation